2020
DOI: 10.24293/ijcpml.v26i3.1597
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Neutrophil-Lymphocyte Ratio in Diagnosis of Autism Spectrum Disorders

Abstract: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder, progressive disruption of brain development and synaptic connections, which causes impaired communication and behavioral disorders. However, the etiology is unknown. A damaged perinatal environment causes chronic nerve inflammation in genetically susceptible children of ASD, dysregulation of the immune system, which leads to ASD. The ratio of Neutrophil to Lymphocyte (NLR) as one of the markers of inflammation is frequently associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Despite the fact that numerous studies have discovered elevations in inflammatory cytokines in ASD, few have isolated and stimulated circulating monocytes to uncover dynamic responses of these cells in children with ASD. These studies' findings revealed that children with ASD have more monocytes than usual 33,34 and neutrophiles 35,36 refuting the conclusions of Ellul et al, 2022 and the current investigation, which found no differences between the monocytes from ASD and controls as well neutrophils. But compared to the control group, our findings showed that the ASD group had more total WBCs and lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
“…Despite the fact that numerous studies have discovered elevations in inflammatory cytokines in ASD, few have isolated and stimulated circulating monocytes to uncover dynamic responses of these cells in children with ASD. These studies' findings revealed that children with ASD have more monocytes than usual 33,34 and neutrophiles 35,36 refuting the conclusions of Ellul et al, 2022 and the current investigation, which found no differences between the monocytes from ASD and controls as well neutrophils. But compared to the control group, our findings showed that the ASD group had more total WBCs and lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
“…This data were recorded for eight years children (Prevention, 2021). For Indonesia, the growth rate is 1.14%, and autism is estimated to affect about 2.4 million people, where the increase is approximately five hundred people per year (Sari et al, 2020).…”
Section: Epidemiology Of Autismmentioning
confidence: 99%